Cellulase Production by Aspergillus niger ATCC 16888 on Copra Waste from Coconut Milk Process In Layered Packed-bed Bioreactor - T. Chysirichote (My University, 2018)
Solid-state fermentation (SSF) has been used to produce value-added products from agricultural and food processing wastes, but the majority of SSF production has been conducted on a small scale due to the limitations of heat and mass transfer.This research aimed to reduce the temperature changes in packed-bed bioreactor during the cellulase fermentation of Aspergillus niger ATCC 16888 on copra waste from coconut milk process.The three configurations of bioreactor used in this study consisted of one-(control), two-and three-layered packed-bed bioreactors.Total volumes of packed-bed bioreactor and bed material were 127 and 57 L, respectively.The sterilized air 30 °C was forced from the bottom of bioreactor at 0.20 vvm.The highest cellulase production (5.0 ± 0.4 FPU g -1 DS ) was obtained from the bottom zone of the three-layered bioreactor after fermenting for 1 d.However, the greatest growth was found at the top one, in which a large amount of aerial mycelium was detected.
Keywords: Copra; Aspergillus niger; Biofuel production and bioconversion